Human-Elephant Conflict: A Review of Current Management Strategies and Future Directions - Shaffer, L. Jen; Khadka, Kapil K.; Van Den Hoek, Jamon; Naithani, Kusum J. (Frontiers in Ecology and Evolution, 2019)
Human-elephant conflict is a major conservation concern in elephant range countries. A variety of management strategies have been developed and are practiced at different scales for preventing and mitigating human-elephant conflict. However, human-elephant conflict remains pervasive as the majority of existing prevention strategies are driven by site-specific factors that only offer short-term solutions, while mitigation strategies frequently transfer conflict risk from one place to another. Here, we review current human-elephant conflict management strategies and describe an interdisciplinary conceptual approach to manage species coexistence over the long-term. Our proposed model identifies shared resource use between humans and elephants at different spatial and temporal scales for development of long-term solutions. The model also highlights the importance of including anthropological and geographical knowledge to find sustainable solutions to managing human-elephant conflict.